EMBRIOLOGI MANUSIA DALAM PERSPEKTIF AL-QUR’AN - Abdul Halim Nasution (NIZHAMIYAH, 2020)
The study of the creation of human biological not only in the realm of science aspect, but the Qur’an which was revealed 15 centuries ago has also informed the creation of human from embryology. The Qur’an notifies that the stage creation of human development is started from the pra-nuthfah, which is meant that the creation of sperm cells from the extract of clay namely main daafiq (the fluid ejected), main mahiin (the liquid disdained), maniyy yumna (semen emitted), nuthfah (spermatozoa). The next stage is ‘alaqah (blastocyst), and then mudhgah (embryo), and the last stage is the process of the forming bones and muscles to become the perfect creature to receive the spirit.